SIKAP ASERTIF DAN PERAN KELUARGA TERHADAP ANAK - Budiyono, Alief (Fakultas Dakwah IAIN Purwokerto, 2012)
Assertiveness is a behavior of a person to be able to express opinions, desires,feelings and beliefs to the others directly, honestly and transparently. Assertiveness is not adefault behavior but it can be learned through the environment. The family is the primaryenvironment first known by a child. Therefore the family is obliged to provide good care ofa child. With the caring and education in the family a child will develop assertivenessoptimally.